Potential antifungal activity of Cladonia aff. rappii A. Evans - Claudia M. Plaza; Celina Pérez de Salazar; Marietta Vizcaya; C. Gabriela Rodríguez-Castillo; Gerardo E. Medina-Ramírez; Ramón E. Plaza (GarVal Editorial Ltda., 2017)
Context: Lichen is a self-supporting symbiotic organism composed of a fungus and an algal partner. They have manifold biological activities like antiviral, antibiotic, antioxidant, antitumor, allergenic and inhibition of plant growth. Species of Cladonia, have been studied by its antifungal activity. Aims: To evaluate the antifungal activity determination of Cladonia aff. rappii against five yeasts, four of genus Candida and one Cryptococcus, using water, ethanol and dichloromethane extracts. Methods: The evaluation of the antifungal activity was developed by three diffusion methods such as spot-on-a-lawn, disc diffusion and well diffusion. Additionally, the values of minimal inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) were determined. Results: Based on the experimental results obtained, the best antifungal activity was using ethanol extract at 20 mg/mL against Candida albicans, applying the three diffusion methods above mentioned. With ethanol extract, the lower MIC was against Candida glabrata and the lower MFC were with Candida glabrata, C. krusei, C. parapsilosis and C. tropicalis. The dichloromethane extract presented the lowest MIC and MFC against C. neoformans. Not activity was observed with aqueous extract. Conclusions: The present study revealed antifungal and fungicidal activity in the extract of lichen Cladonia aff. rappii.